Re-creating Indigenous Architectural Knowledge in Arctic Canada and Norway - Mackin, Nancy (Protection of Cultural Heritage, 2020)
Long resident peoples including Gwich’in, Inuvialuit, Copper Inuit, and Sami, Coast Salish and others have learned over countless generations of observation and experimentation to construct place-specific, biomimetic architecture. To learn more about the heritage value of long-resident peoples’ architecture, and to discover how their architecture can selectively inform adaptable architecture of the future. we engaged Inuit and First Nations knowledge-holders and young people in re-creating tradition-based shelters and housing. During the reconstructions, children and Elders alike expressed their enthusiasm and pride in the inventiveness and usefulness of their ancestral architectural wisdom. Several of the structures created during this research are still standing years later and continue to serve as emergency shelters for food harvesters. During extreme weather, the shelters contribute to a potentially widespread network of food harvester dwellings that would facilitate revitalization of traditional foodways. The re-creations indicate that building materials, forms, assembly technologies, and other considerations from the architecture of Indigenous peoples provide a valuable heritage resource for architects of the future.